Translocation pause of remdesivir-containing primer/template RNA duplex within SARS-CoV-2’s RNA polymerase complexes - Shi, Yuanjun; Wang, Jimin; Batista, Victor S. (Frontiers in Molecular Biosciences, 2022)
The mechanistic effect of remdesivir incorporation into the RNA primer by the RNA-dependent RNA polymerase (RdRp) of SARS-CoV-2 remains to be fully established at the molecular level. Here, we compare molecular dynamics (MD) simulations after incorporation of either remdesivir monophosphate (RMP) or adenosine monophosphate (AMP). We find that the Mg2+-pyrophosphate (PPi) binds more tightly to the polymerase when the added RMP is at the third primer position than in the AMP added complex. The increased affinity of Mg2+-PPi to the RMP-added primer/template (P/T) RNA duplex complex introduce a new hydrogen bond of a substituted cyano group in RMP with the K593 sidechain and disrupts other hydrogen bonds in a network essential for translocation of the P/T duplex product, which opens a vacant NTP-binding site necessary for next primer extension. Furthermore, steric interactions between the sidechain of S861 and the 1'-cyano group of RMP at position i+3 hinders translocation of RMP to the i+4 position, where i stands for the insertion site. These findings are particularly valuable to guide the design of more effective inhibitors of SARS-CoV-2 RNA polymerase.